Movement Matters! Understanding the Developmental Trajectory of Embodied Planning - Musculus, Lisa; Ruggeri, Azzurra; Raab, Markus (Frontiers in Psychology, 2021)
Humans motor skills are exceptional when compared to other species, no less than their cognitive skills. In this paper, we suggest that ``movement matters!'', implying that motor development is a crucial driving force of cognitive development, much more impactful than previously acknowledged. Thus, we argue that to fully understand and explain developmental changes, it is necessary to consider the interaction of motor and cognitive skills. We exemplify this argument by introducing the concept of ``embodied planning,'' which takes an embodied cognition perspective on planning. From this integrated, comprehensive framework, we present a novel climbing paradigm as the ideal testbed to explore the development of embodied planning across the lifespan. Finally, we outline future research directions and discuss practical applications of the work on developmental embodied planning for robotics, sports, and education.